Analisis Variasi Ketinggian Penyiraman Kabut Menggunakan Nozzle Terhadap Pertumbuhan Persemaian Tanaman Sawi Hijau ( Brassica juncea L) - Sumarsono, Joko; Widhiantari, Ida Ayu; De Side, Gagassage Nanaluih; Abdullah, Sirajuddin Haji; Priyati, Asih; Dewi, Endang Purnama; Amaliah, Wenny; Pangestuti, Rika Wulandari (Jurnal Teknologi Pertanian Andalas, 2025)
The success rate in the seedling process is ofte hampered by inappropriate watering, which can cause the seedlings to rot and die. To overcome this problem, an efficient watering system with a high degree of precision is required. Mist irrigation is one of the appropriate methods because micro-sized water droplets are sprayed to maintain air humidity and reduce the rate of transpiration. This study aims to optimize the application of mist irrigation by evaluating the effect of nozzle height variations on plant growth. Using an experimental method, the variations included nozzle heights of 20 cm, 25 cm, and 30 cm. The parameters measured in this study included water discharge, plant height, number of leaves, and leaf area. The results showed that a watering height of 25 cm produced the best plant growth. The results of this study show that specific adjustment of the nozzle height is very important for improving the efficiency of mist irrigation in the seedling process. Keywords: mist irrigation, seedling, green mustard